Endothelial dysfunction and periodontitis: The role of inflammatory serum biomarkers - Reila Tainá Mendes; Daniel Fernandes (Wolters Kluwer Medknow Publications, 2016)
Introduction: Periodontitis is a local chronic inflammation with systemic consequences. Many disorders are associated with periodontitis such as diabetes, high-serum low-density lipoprotein (LDL), and premature birth. Cardiovascular disease does not correspond to a classic risk factor for periodontitis but evidence suggests that endothelial dysfunction due to systemic inflammation may be the link between both pathologies. The aim of this study was to review the literature regarding endothelial dysfunction and periodontitis and to establish a possible link through systemic inflammatory biomarkers. Methods: We searched the terms "periodontitis and endothelial dysfunction" and "periodontal disease and endothelial dysfunction" in the following four databases: PubMed, Cochrane, Bibliografia Brasileira de Odontologia-Brazilian Bibliography in Dentistry (BBO), and Embase. Results: Both diseases share same systemic biomarkers. Conclusion: Endothelial dysfunction may be the link between periodontitis and other diseases such as cardiovascular ones.